2013
DOI: 10.3892/or.2013.2887
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Slit2 promotes growth and motility in gastric cancer cells via activation of AKT/β-catenin

Abstract: We previously showed that Slit2 was highly expressed in gastric cancer tissues that exhibit less advanced clinicopathological features, suggesting a tumor suppressor role for Slit2. In the present study, we investigated the effects of Slit2 knockdown on gastric cancer cells. Slit2-specific shRNAs were used to generate Slit2-knockdown SGC-7901 gastric cancer cells. Cell proliferation assay, Annexin V/PI double staining and cell cycle analysis were used to investigate the role of Slit2 knockdown in cell growth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Furthermore, frequent and diverse somatic aberrations in SLIT/ROBO signalling pathway have been reported in B20% of pancreatic adenocarcinomas 38 . Knockdown of SLIT2 promotes growth and motility in GC cells via activation of AKT/CTNNB1 (b-catenin), suggesting tumour suppressor role 39 . On the basis of these findings, the Ephrins and SLIT/ROBO signalling pathways may be involved in the development of GC and could be a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, frequent and diverse somatic aberrations in SLIT/ROBO signalling pathway have been reported in B20% of pancreatic adenocarcinomas 38 . Knockdown of SLIT2 promotes growth and motility in GC cells via activation of AKT/CTNNB1 (b-catenin), suggesting tumour suppressor role 39 . On the basis of these findings, the Ephrins and SLIT/ROBO signalling pathways may be involved in the development of GC and could be a therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…SLIT2 regulates the β-catenin/TCF and PI3K/AKT signaling pathways and enhances cell-cell adhesion in breast cancer (10). Knockdown of SLIT2 promotes gastric cancer cell proliferation and migration via activation of AKT/β-catenin signaling (11). SLIT2 and SLIT3 are frequently methylated and downregulated in various cancers such as breast (12), colorectal (13), cervical (14), and lung (12), but their methylation status in gastric cancer has not been unequivocally defined.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study identified Slit2 as a diagnosis and prognosis marker in gastric cancer. Mechanistically, it participates in gastric cancer oncogenesis and metastasis through regulating the AKT/β-catenin pathway (15,16).To the best of our knowledge, the expression pattern of Slit2 and its correlation with clinicpathological parameters of PTC has not been previously reported. In the present study, we examined Slit2 expression in transcriptional and protein level, and then analyzed the correlation between Slit2 expression and the clinicopatholocical characteristics of PTC.…”
mentioning
confidence: 87%
“…Thus, the role of Slit2 in cancer is distinct depending on the cancer type. Our previous studies (15,16) in gastric cancer indicated that Slit2 is a tumor suppressor. The expression of Slit2 was higher in gastric patients with less advanced clinicopathological features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation